Study of synthesis mechanism, structural, optical and luminescent properties of bluish-violet rare earth doped KSrVO4: Nd3+ nano powders - Sharma P.; Singh P.; Kamni (My University, 2025)
In this study, we have developed Nd3+ doped KSrVO4 synthesized via combustion synthesis route. Herein, we report the variation in the lattice parameters and confirmed the orthorhombic phase for the as-synthesized blank and KSr(1-x)VO4: xNd3+ (x = 0.0025 – 0.03) phosphor investigated by powder XRD system. The morphology was procured via SEM and TEM and the elemental analysis was carried out with EDAX. UV–Vis spectroscopy showed the variations in the band gap energy values. The Photoluminescence (PL) spectra shows three sharp peaks in the emission spectra located at 424 nm, 486 nm and 507 nm in the visible spectra. As a function of Nd3+ concentration, it was observed that 0.05 mol% Nd3+ doped nanophosphors exhibit the strongest emission intensity. Concentration quenching is induced mainly due to the energy transfer among nearby neighboring ions. The enhanced emission intensity of the phosphor with doping suggests that it may be used in display applications. © 2021 Elsevier B.V.